2011
DOI: 10.1016/j.ijdevneu.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction in the rat during pregnancy and/or lactation alters cognitive and anxiety behaviors of female offspring

Abstract: Maternal protein deficiencies can developmentally program offspring to lifelong dysfunction of many physiological systems. We hypothesized that maternal isocaloric low protein diet during fetal and early postnatal development would negatively affect female offspring anxiety, exploration, associative learning and motivation as measured by the elevated plus maze (EPM), open field test (OFT), operant conditioning and the progressive ratio task, respectively. Control mothers (C) received a 20% casein diet and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…At the long-term period, reports on infants having suffered from FGR showed neurocognitive difficulties [30] that were even more prevalent in those cases with evident signs of placental insufficiency [31] . In basic research, FGR animal models including UN, a low-protein diet, and PU showed higher degrees of anxiety, reduced social interaction, and depression-related behaviors [16,29,32] , as well as learning, short-term memory, and attention problems [21,[33][34][35] . Our results support the notion that severity and type of insult during the prenatal period results in a differential effect on neurobehavior, with more remarkable changes in the PU model.…”
Section: Discussionmentioning
confidence: 99%
“…At the long-term period, reports on infants having suffered from FGR showed neurocognitive difficulties [30] that were even more prevalent in those cases with evident signs of placental insufficiency [31] . In basic research, FGR animal models including UN, a low-protein diet, and PU showed higher degrees of anxiety, reduced social interaction, and depression-related behaviors [16,29,32] , as well as learning, short-term memory, and attention problems [21,[33][34][35] . Our results support the notion that severity and type of insult during the prenatal period results in a differential effect on neurobehavior, with more remarkable changes in the PU model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased 2-AG in hippocampus was associated to mitigation of the cognitive alterations in severely undernourished mice supplemented with a diet rich in fish oil, an important source of n-3 PUFAs [78], although the opposite has been described in an animal model of schizophrenia [79]. In the context of nutritional programming, emotional responses and cognitive performance have been found to be affected after exposure to undernutrition during critical windows of development and/or in new born small for gestational age [14, 20, 80] and in a sex specific-manner [81, 82]. Despite this evidence, the increased levels of 2-AG, AEA and AA we found in the hippocampus are difficult to interpret, considering that CB 1 receptor activation by endocannabinoids may mediate bimodal opposite responses depending on the differential distribution of CB 1 in distinct neuronal populations [29].…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of research has focused on developmental programming and more recently on epigenetic modifications [5]. In contrast with the female F 2 by paternal linage behavior, female F 1 from our maternal protein restricted model showed decreased open arm time and distance in both groups restricted during pregnancy, which means increased anxiety behavior in the EPM, associated with higher corticosterone serum levels [25]. Embryo and fetal development conditions in female F 1 from restricted mothers and female F 2 from paternal protein restricted linage were different, since F 0 restricted mothers presented higher corticosterone serum levels in comparison with control mothers while fathers (F 1 ) from restricted mothers had lower corticosterone serum levels.…”
Section: Discussionmentioning
confidence: 70%
“…We previously reported that prenatal protein restriction in the rat reduces fetal (F 1 ) brain docosahexaenoic acid content [24] and gender specific outcomes in both EPM and open field test in adult F 1 of F 0 mothers on a maternal low protein diet during pregnancy and/or lactation [18,25]. F 1 male showed increased approach and less avoidance behavior (less anxiety) and thus exhibited disinhibition of avoidance as compared to controls.…”
Section: Discussionmentioning
confidence: 99%